Long term tolerability and clinical outcomes associated with tocilizumab in the treatment of refractory antibody mediated rejection (AMR) in pediatric renal transplant recipients. Issue 8 (12th June 2022) - Pearl, Meghan; Weng, Patricia L.; Chen, Lucia; Dokras, Aditi; Pizzo, Helen; Garrison, Jonathan; Butler, Carrie; Zhang, Jennifer; Reed, Elaine F; Kim, Irene K.; Choi, Jua; Haas, Mark; et al.
Abstract: Background: Treatment options for antibody‐mediated rejection (AMR) are limited. Recent studies have shown that inhibition of interleukin‐6 (IL‐6)/interleukin‐6 receptor (IL‐6R) signaling can reduce inflammation and slow AMR progression. Methods: We report our experience using monthly tocilizumab (anti‐IL6R) in 25 pediatric renal transplant recipients with AMR, refractory to IVIg/Rituximab. From January 2013 to June 2019, a median (IQR) of 12 (6.019.0) doses of tocilizumab were given per patient. Serial assessments of renal function, biopsy findings, and HLA DSA (by immunodominant HLA DSA [iDSA] and relative intensity score [RIS]) were performed. Results: Median (IQR) time from transplant to AMR was 41.4 (24.367.7) months, and time from AMR to first tocilizumab was 10.6 (8.317.6) months. At median (IQR) follow up of 15.8 (8.435.7) months post‐tocilizumab initiation, renal function was stable except for 1 allograft loss. There was no significant decrease in iDSA or RIS. Follow up biopsies showed reduction in peritubular capillaritis ( p = .015) and C4d scoring ( p = .009). The most frequent adverse events were cytopenias. Conclusions: Tocilizumab in pediatric patients with refractory AMR was well tolerated and appeared to stabilize renal function. The utility of tocilizumab in the treatment of AMR in this population should be further explored.